2t+5+3t-4t=2+3

Simple and best practice solution for 2t+5+3t-4t=2+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t+5+3t-4t=2+3 equation:


Simplifying
2t + 5 + 3t + -4t = 2 + 3

Reorder the terms:
5 + 2t + 3t + -4t = 2 + 3

Combine like terms: 2t + 3t = 5t
5 + 5t + -4t = 2 + 3

Combine like terms: 5t + -4t = 1t
5 + 1t = 2 + 3

Combine like terms: 2 + 3 = 5
5 + 1t = 5

Add '-5' to each side of the equation.
5 + -5 + 1t = 5 + -5

Combine like terms: 5 + -5 = 0
0 + 1t = 5 + -5
1t = 5 + -5

Combine like terms: 5 + -5 = 0
1t = 0

Solving
1t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '1'.
t = 0

Simplifying
t = 0

See similar equations:

| -7x-8y=19 | | -5/9m=-1/4 | | -20=5/13x | | -20x=5/13x | | 10p+6=4p+22 | | 3(2x+9)=-33+12 | | 20x+11/12-19x=5/24 | | -4y-2=-3y-9 | | -43=x | | -(-2a+2)=-6(3+9a) | | t-15=19 | | 25+5-10(y+4)= | | 4a+12=4a+6a | | 2x+5=3x+-1 | | 7(8+3x)=19 | | 8t+3(3t-2)=-5t-10 | | 5-2x/7=9/14 | | 5(3x-6)-3(x+1)-19x= | | 1/8+y=-7/16 | | -96=z+-83 | | 3x-3=21x+9 | | 8x+7=87 | | 4(-4y^5)= | | 3x=2x+17 | | x-1/7=13/14 | | (6x+1)(x-7)=0 | | 3z-5-z+3=0 | | 5/8x+7=-3/8x | | 14x-13/8-13x=10/8+3/8 | | -0.8x+0.5x-6=9 | | 6n^2=-8n-1 | | x-1/3=2x/5+1/15 |

Equations solver categories